Exploring Current Methods and Trends in Text Summarization: A Systematic Mapping Study - Ahmad Raddi, Muhammad Faris Faisal; Hassan, Rohayanti; Zakaria, Noor Hidayah; Sahid, Mohd Zanes; Omar, Nurul Aswa; Firosha, Ardian (JOIV : International Journal on Informatics Visualization, 2024)
This paper presents a systematic mapping study of the current methods and trends in text summarization, a challenging task in natural language processing that aims to condense information from one or multiple documents into a concise and coherent summary. The paper focuses on applying text summarization for the Malay language, which has received less attention than other languages. The paper employs a three-phased quality assessment procedure to filter and analyze 27 peer-reviewed publications from seven prominent digital libraries, covering 2016 to 2024. The paper addresses two research questions: (1) What is the extent of research on text summarization, especially for the Malay language and the education domain? and (2) What are the current methods and approaches employed in text summarization, with a focus on addressing specific problems and language contexts? The paper synthesizes and discusses the findings from the literature review and provides insights and recommendations for future research directions in text summarization. The paper contributes to advancing knowledge and understanding of the state-of-the-art techniques and challenges in text summarization, particularly for the Malay language.